Assessing Psychosocial Factors in Depressed Patients – Accordance of Patient’s and Physician’s Assessment - Stojanović-Špehar, Stanislava (Array, 2011)
Aim of this study was to investigate the differences in the assessment of psychosocial factors by depressed and non depressed patients, and their congruence with physicians’ assessment for both groups. The cross-sectional study was conducted in three family physicians’ practices in Zagreb, Croatia, during 2007. Sample of depressed patients included 76 patients out of 85, and randomized comparison group of 189 out of 235. Questionnaire recommended by the European Guidelines on Cardiovascular Disease Prevention in Clinical Practice was used for the assessment of psychosocial factors. Depressed patients significantly more frequently reported about social isolation (palone=0.013 ; pclose confident=0.005 ; phelp=0.001), family stress (p<0.001), work stress (pappropriate reward=0.029) and lower life satisfaction (p<0.001) than non depressed. Their worse psychosocial functioning was noticed by family physicians who assessed social isolation (palone= 0.013 ; pclose confident=0.032), family stress (p<0.001) and life satisfaction (p<0.001) significantly lower for depressed patients than for the random sample. Incongruence between family physicians and depressed patients assessment was valued by physicians to be of higher economic status (p<0.001), and more intense family stress (p<0.001). Assessment of psychosocial factors varied within the group of depressed patients and the random sample assessed either by themselves or by physicians. Congruence between family physicians and non depressed patients in the assessment of observed psychosocial factors was better than between physicians and depressed patients.